Application of metabolomics in quality control of traditional Chinese medicines: a review - Ji, Peiran; Yang, Xinquan; Zhao, Xiangsheng (Frontiers in Plant Science, 2024)
Plant metabolites are the components endowing traditional Chinese medicine (TCM) with therapeutic effects, and, simultaneously, they are the primary targets for quality control. From germplasm selection and origin determination to field management, growth duration, harvesting and processing, and, finally, storage and transportation, each step profoundly influences TCM quality. The complexity of these plant or herb metabolites poses numerous quality control challenges. Metabolomics, as a comprehensive and systematic approach, has demonstrated value in this field. This technique not only meets the requirements for studying the complex mechanisms of TCM but also has significant advantages in identifying the TCM components, including active components. Therefore, in this article, several key factors affecting the chemical characteristics and quality traits of TCM, including their origin, harvesting period, medicinal parts, and processing methods, are researched. Additionally, the current challenges of integrating metabolomics with other omics technologies (transcriptomics, spatial metabolomics, etc.) are discussed. Furthermore, a future development trends and prospects are highlighted. With the continuous deepening of research and ongoing updates in technological capabilities, metabolomics will play an increasingly important role in the quality control of TCM, providing more scientific and robust support for quality assurance and safety evaluation.